Exploring managerial intentionality - Thomas Hutzschenreuter; Un-Seok Han; Ingo Kleindienst (Managerial and Decision Economics, 2019)
To enable a better understanding of individual and, as a logical extension, organizational behavior, we set forth a theoretical framework of managerial intentionality. At its core are the concepts of desire and belief, which together form intentions. We argue that it is these intentions that may substantially affect strategic choices and, by that, organizational change. Exploring managerial intentionality, we acknowledge a central building block of cognitive science, which contrary to representations and computations has, by and large, been neglected in the management and organization literatures. We use the framework to explore the intrapersonal and interpersonal role of managerial intentionality as well as its effectiveness in an organizational context. We also clarify the differences to related concepts and discuss implications for future research. In doing so, we contribute to the overall objective of increasing our understanding of managerial action and organizational behavior.
Keywords: 650